Parallel Sparse Direct Solver for Integrated Circuit Simulation - Chen, Xiaoming; Wang, Yu.; Yang, Huazhong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes algorithmic methods and parallelization techniques to design a parallel sparse direct solver which is specifically targeted at integrated circuit simulation problems. The authors describe a complete flow and detailed parallel algorithms of the sparse direct solver. They also show how to improve the performance by simple but effective numerical techniques. The sparse direct solver techniques described can be applied to any SPICE-like integrated circuit simulator and have been proven to be high-performance in actual circuit simulation. Readers will benefit from the state-of-the-art parallel integrated circuit simulation techniques described in this book, especially the latest parallel sparse matrix solution techniques. · Introduces complicated algorithms of sparse linear solvers, using concise principles and simple examples, without complex theory or lengthy derivations; · Describes a parallel sparse direct solver that can be adopted to accelerate any SPICE-like integrated circuit simulator and makes circuit simulators more efficient on modern parallel processors; · Uses experimental results from practical applications to demonstrate the performance of the parallel sparse direct solver.
Introduction -- Related Work -- Overall Solver Flow -- Parallel Sparse Left-Looking Algorithm -- Improvement Techniques -- Test Results -- Performance Model -- Conclusions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation